Hardella thurjii (Gray 1831) – Crowned River Turtle - Das, Indraneil; Bhupathy, S. (Chelonian Research Foundation, 2008)
The crowned river turtle, Hardella thurjii (Family Geoemydidae), is a large (CL to 65 cm) freshwater turtle, largely confined to lentic waters in the Indian subcontinent. The species shows extreme sexual size dimorphism, females attaining a length over three times that of the males. Only plant matter is taken by the species in some areas, but elsewhere prawn or fish may be taken, possibly as carrion. Courtship and mating take place during the summer months in northern India, and 8–19 ellipsoidal eggs may be produced. Heavy exploitation for its flesh and extensive wetland development projects are among the factors suspected to have made the turtle rare in localities where it was once common, although there is some evidence that the species is difficult to observe in the wild.